Analyzing fınancial performance of Turkish deposit banks using TOPSIS method - Ova, Alper (Pamukkale Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2021)
ABSTRACT: Banking industry is indisputably the biggest part of the financial sector in Turkey. Regarding the importance of banking industry, this study aimed to investigate the financial performance of Turkish banking industry for the period between 2012 and 2019 using TOPSIS method. For this purpose, firstly ten banks, which had the highest amount of assets, were ranked using eight criteria since these banks represent a great percentage of the banking industry. Secondly, bank ownership types were analyzed and ranked. The results indicate that there is a decline in the performance of state owned banks. Foreign banks founded in Turkey seemed to be the best performing bank type in the last three years. Moreover, in this set of ten banks, the best bank from 2012 to 2017 was a state owned bank, the best bank in 2018 was a foreign bank founded in Turkey and the best bank in 2019 was a privately owned bank.

ÖZET: Bankacılık endüstrisi tartışmasız Türkiye’deki finansal sektörün en büyük parçasıdır. Bankacılık sektörünün önemini dikkate alan bu çalışma, TOPSIS yöntemini kullanarak Türk bankacılık sektörünün finansal performansını 2012-2019 periyodu için araştırmayı amaçlamaktadır. Bu hedef doğrultusunda, ilk olarak bankacılık sektörünün büyük bir kısmını temsil ettiğinden en yüksek aktif büyüklüğe sahip on banka sekiz kriter kullanarak sıralanmıştır. İkinci olarak banka sahiplik tipleri analiz edilmiş ve gerekli sıralama yapılmıştır. Sonuçlara göre, kamu bankalarında bir düşüş gözlenmektedir. Türkiye’de kurulmuş yabancı bankalar son üç yıl içinde en iyi performans gösteren banka tipi olmuştur. Ayrıca bu 10 bankadan oluşan firma seti içinde, 2012’ den 2017’ ye kadar en iyi performans gösteren banka bir kamu sermayeli mevduat bankası olmuş, 2018 yılında Türkiye’de kurulmuş bir yabancı sermayeli banka ve 2019 yılında ise özel sermayeli bir mevduat bankası en iyi performansı göstermiştir.
Türk mevduat bankalarının finansal performanslarının TOPSIS metoduyla analizi
Keywords: Banks; TOPSIS; Financial Performance; Bankalar; Finansal Performans